(untitled) (Innovative Technologica: Methodical Research Journal, 2023)
Many initiatives and technologies are working in the Republic of Uzbekistan to introduce modern plants of the future based on technological processes of managing the activities of industrial enterprises. One consensus is that there should be a classic hierarchical automation system design. The operating system is aligned with support for technology and data functions. It includes technology related processes within the same network infrastructure. To achieve the goal of IT/OT convergence evolutionary transition is preferred in process automation. Difficulties during training the transition is mainly due to the traditional automation architecture, and the main problem is this it will be necessary to distinguish between current and future network architectures. To solve problems, in this article, we describe a desired future scenario for process automation and traffic enforcement. The measured traffic is further analyzed, which reveals shows representative transport characteristics in process automation. Finally, the main challenges and the future directions of system architecture for future factories will consist of improving the quality of the presented, developing the operating system of the technological system based on modern information technologies.